Pengembangan APE Bowling untuk Menstimulus Kemampuan Mengenal Lambang Bilangan Anak Usia 4-5 Tahun di TK Nasrani-2 Medan - Gaberiella U.T.R.Simatupang; Srinahyanti Srinahyanti (FKIP, Universitas Palangka Raya, 2025)
The problem found in this research is that the bowling educational game tool used to stimulate the ability to recognize number symbols in children aged 4-5 years has not been realized. The formulation in this research is 1) What is the level of validity of APE Bowling to stimulate the ability to recognize number symbols in children aged 4-5 years at Kindergarten Nasrani 2 Medan? 2) What is the level of practicality of APE Bowling to stimulate the ability to recognize number symbols in children aged 4-5 years at Christian Kindergarten 2 Medan? . This research is development research using the ADDIE model which consists of five stages, namely analysis, design, development, implementation, and evaluation. The method used in this research is using a questionnaire method. The results of the development research show that the material expert validator's assessment received a score of 93% so that the assessment achieved by the material expert can be said to be